ANALYSIS OF CORRELATION RELATIONS OF PSYCHOPHYSIOLOGICAL INDICATORS OF QUALIFIED BADMINTONISTS - Mishchuk, D. M.; Siui, Santsian (Rehabilitation and Recreation, 2021)
Badminton is one of the fastest growing sports in the world and has a high rating of entertainment. A modern highly qualified athlete who plays badminton must be very well prepared physically, have a good command of various techniques and have a wide arsenal of tactical solutions. Analysis of theoretical and practical experience of training athletes shows that the level of sports results and skills in badminton largely depends on how effectively developed, formed and used are psychophysiological qualities and abilities of athletes. Effective training of young people and successful activities of highly qualified players is impossible without a comprehensive assessment of the physical and psychophysiological condition of badminton players. The effectiveness of highly qualified badminton players depends on the athlete’s ability to perceive, analyze and process information, study psychophysiological functions in order to control the functional state of the athlete and correct the training process is very important. The study involved 34 people, 12 men and 22 women, aged 17–22 years, qualification I category, CMS and MS. With the help of the hardware-software computer complex “Multipsychometer-05” in the block of neurodynamic research the balance of the nervous system and functional mobility of nervous processes were studied (tests “Balance of nervous processes”, “Functional mobility of nervous processes”); in the block of cognitive researches the general cognitive abilities were studied (the test “Advanced progressive Raven matrices”); in the block of researches of cognitive-activity styles various psychoemotional states and field dependence of athletes were studied (test of color choices, “Field independence”). Pearson’s correlation coefficient (r) was used to assess the relationships between different psychophysiological indicators of badminton players. Analysis of the obtained results of correlations shows that neurodynamic characteristics have weak and moderate relationships with cognitive characteristics and psycho-emotional states of athletes, which are characterized by features of cognitive-activity styles (p <0.05). Thus, the formation of the cognitive sphere and cognitive-activity styles of the athlete in addition to neurodynamic characteristics, are also influenced by other factors.